World economy burdened by imbalances - Günter Großer; Günter Weinert (Intereconomics, 1988)
The development of the world economy is overshadowed by the slump of the dollar and the collapse of international stockmarkets. What are the prospects for the world economy in 1988?
Keywords: 330; Economic trends